MAIN CHARACTERISTICS OF MATERIALS USED IN METAL CONSTRUCTION - SH.A. Egamberdiyeva (Journals Park Publishing, 2024)
This article is on the topic of "the main characteristics of materials used in metal construction", it provides information about the types of metals, their properties and the advantages of metal construction.
Keywords: metals, strength limit, ligering, ferrite, flowability, recovery, load accumulation, QMQ.